Pengaruh Dana Perimbangan, Pendapatan Asli Daerah, dan Pertumbuhan Ekonomi Terhadap Indeks Pembangunan Manusia Di Kabupaten Kepulauan Yapen - De Fretes, Pieter (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
The purpose of this research is to know the influence of balancing fund (general allocation fund, special allocation fund, revenue sharing), local revenue (PAD), and economic growth on human development index (HDI) in Yapen Islands District. Balancing funds and PAD are funded by capital expenditures, while economic growth is a control variable based on the theoretical study of the UNDP's Human Development Report. The analytical method used is multiple linear regression. The result of research estimation shows that the ratio of DAK and PAD to capital expenditure and economic growth have positive and significant effect on HDI while DAU variable has significant negative effect. For DBH ratio to capital expenditure becomes the only variable that does not significantly affect HDI.